Manifest Quasi-Universals and Embedding Conceptual Clusters - Jaap van Brakel; Lin Ma (Asian Studies, 2022)
We start this article with a discussion of the problematics involved in translating into modern English a (modern) Chinese text concerning a classical Chinese notion, namely qíng 情. Then, we suggest that it is necessary to distinguish between two levels on which a language is used. The first is the manifest level, where one finds family resemblance between, say, Chinese nù 怒 and English “anger”. The second is the generic level, where one finds qíng in classical Chinese, qínggaˇn in modern Chinese, and emotion(s) in English. We argue that the meanings of words at the generic level can only be accessed via the manifest level. It is misleading to directly identify and compare notions at the generic level (in this case, emotion(s) in English and qíng in Chinese). We call the connections at the manifest level “quasi-universals”, and we refer to the notions at the generic level as “embedding conceptual clusters”.